Lord, have mercy : - Wolfteich, Claire E. (Jossey-Bass, 2006)
Wolfteich provides carefully researched case studies from suburban Miami to the turmoil of apartheid South Africa, analyzing the relation of prayer to various human purposes. She guides the reader through the ambiguities of each case, giving no easy answers, teaching by asking questions. But on another, more personal level, the book is an ongoing conversation with the author. Her voice comes through again and again—quiet, intelligent, unpretentious—exposing her own vulnerabilities.